Oxford Energy Forum, Issue 96 - Bassam Fattouh; Laura El-Katiri (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2014)
Oil has defined the modern-day development of the Gulf region in a way seen in no other place in the world; together, the six members of the Gulf Cooperation Council (GCC), Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates, are home to around a third of known global reserves of oil, and nearly a quarter of its natural gas. Saudi Arabia remains the world's most important producer of conventional oil, and continues to hold the majority of the world's spare capacity, while Qatar has become the world's largest producer of liquefied natural gas. This reflects the GCC states' continuing pivotal role on global energy markets as a key centre of world energy supply. The fast-track economic growth and development experienced by the GCC economies since the mid-20th century in particular, however, has also left its toll on the region's energy profile. No longer just global suppliers of energy, the GCC states have become a key centre of energy demand growth in their own right, accounting to a large extent for projections such as those by the IEA that see the Middle East alongside Asia as the world's future energy demand growth centres well into the 2030s. This issue of OEF reflects on the variety of options and challenges faced by the GCC states more than a decade into the new millennium, and offers perspectives on future policy choices inside one of the world's most important group of energy producers.
Keywords: 330